n-(CdMgTe/CdTe)/(p-(CdTe/ZnCdTe/ZnTe)/p-GaAs heterostructure diode for photosensor applications - Yahia, I. S.; AlFaify, S.; Abutalib, M. M.; Chusnutdinow, S.; Wojtowicz, T.; Karczewski, G.; El-Bashir, S. M. (Springer Heidelberg, 2016)
High quality n-(CdMgTe:I/n-CdTe: I)/(p-CdTe:N/p-ZnCdTe:N/p-ZnTe:N)/p-GaAs heterojunction diodes have been fabricated by molecular beam epitaxial growth. The illumination effect on the complex impedance and conductivity of heterostructure diode was investigated. The illumination intensities were taken up to the 200 mW/cm(2) with frequency range of 42 Hz to 1 MHz. The observed real and imaginary parts of the complex impedance were strongly dependent on the illumination frequency. The inverse relation was observed between the illumination intensity and the complex impedance. The relaxation mechanism of the diode was analyzed by the Cole-Cole plots. The radius of the Cole-Cole curve decreases with increasing illumination intensity. This suggests a mechanism of illumination dependent on the relaxation process. It is also found that the conductivity increases linearly with increasing the illumination intensity. We can conclude that the new design heterostructure diode in our work is a good candidate in photodetector and optoelectronic applications.
Keywords: Impedance Spectroscopy; Solar-Cell; Frequency